Analisis Pengaruh Budaya Organisasi, Work Enggamenent (Keterlibatan Kerja), Kinerja Terhadap Quality Of Worklife (Kualitas Kehidupan Kerja) Guru, Pada Yayasan Pendidikan Karya Bahana Mandiri - Sumini; Rakhmat; Andi Muhammad Sadli (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
The quality of education is determined by the quality of teachers' work life as the main educators in schools. Some factors that affect the quality of teachers' work life include organizational culture, work engagement, and teacher performance. This study aims to determine the effect of organizational culture, work involvement, performance on the quality of work life of vocational teachers at Karya Bahana Mandiri Education Foundation. The research approach used is a quantitative approach, using measuring instruments in the form of an organizational culture scale, work engagement scale, performance scale, and quality of work life scale. The population of this study was 103 teachers of Karya Bahana Mandiri Education Foundation. From the total population the researcher took a sample of 51 respondents. Sampling was determined using the Krejcie-Mogran table. The data collection process uses a Likert scale, while data analysis uses Cronbach's Alpha with the help of the SPSS for Windows version 26 program. The results of the t test the t value of 10.954 is greater than> t table 2.010, so it can be concluded that HO is rejected and H1 is accepted, which means that partially states